THE INFLUENCE OF HEALTH EDUCATION MEDIA BOOKLET ON FOOT HYGIENE CARE ON DIABETES MELLITUS PATIENTS AT MELIA MEDIKA CLINIC PAMEKASAN - Vendi Eko Kurniawan; Muhammad Rifki Ramadani; Fakhrun Nisa’ Fiddaroini (PRIMA WIYATA HEALTH, 2026)
Background: Lack of knowledge about proper foot hygiene is a risk factor for diabetic foot ulcers in patients with diabetes mellitus. Health education using booklets is seen as an educational strategy that can improve understanding and practice of foot care. Objective: This study aims to analyze the effect of health education using booklet media on foot hygiene care in diabetes mellitus patients at the Melia Medika Pamekasan Clinic. Methods: This study used a quasi-experimental design with a pretest–posttest approach with a control group. The sample consisted of 46 respondents, divided into an intervention group and a control group of 23 respondents each, selected using a simple random sampling technique. The intervention group received health education using a booklet, while the control group received health education without a booklet. Data were collected using a foot hygiene care questionnaire and analyzed using the Wilcoxon Signed Rank Test with a significance level of 0.05. Results: The analysis showed a difference in foot hygiene scores before and after the intervention in the group receiving health education using booklets (p < 0.05). Changes in scores in the control group did not show a significant increase compared to the intervention group. Conclusion: Health education using booklets has significantly improved foot hygiene care in patients with diabetes mellitus. Booklets can be used as a supportive educational tool for the ongoing prevention of diabetic foot complications.